Impact of Pressure on the Parameters of Pea Straw Compaction (Agricultural Engineering, 2019)
This paper presents the results of pea straw compaction efficiency tests. The compliance of the tested material to pressure agglomeration was assessed depending on the compaction pressure used (45-113 MPa). The compaction was carried out using a Zwick testing machine, type Z020/TN2S, and a closed die pressing unit. It was found that, along with the pressure increase, the material density in the chamber increased (from 1.255 to 1.76 g∙cm−3), as well as the agglomerate's density (from 0.739 to 1.05 g∙cm−3) and the product's mechanical resistance (from 0.31 to 0.69 MPa). Increasing the compaction pressure in the analyzed range increased the unit value of compaction work, from 17.16 to 34.27 J·g−1.